2019
DOI: 10.1016/j.ijrobp.2019.06.1975
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy and Chemotherapy Offer a Recurrence and Survival Benefit in Patients with Resected Perihilar Cholangiocarcinoma

Abstract: Conclusion: The majority of HCC patients with LV <1000 ml were ineligible to SBRT and frequently required dose compromization for hypofractionated photon radiotherapy. Strikingly, PBT permitted these patients to undergo ablative radiation treatment and offered substantial local control benefits with <5% of RILD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Subgroup analyses of Bismuth type III-IV patients with R0 resection revealed that adjuvant chemotherapy produced significant survival benefits when compared with surgery alone (electronic supplementary Fig. S4); a similar result was reported by Im et al 53 However, a relatively low percentage of patients received adjuvant chemotherapy and there was a large difference in chemotherapy percentages between the LS and OP groups. A previous study demonstrated that LS is associated with greater rates of compliance with guidelines for adjuvant chemotherapy, as well as a slightly shorter time before initiation of chemotherapy.…”
Section: Discussionsupporting
confidence: 81%
“…Subgroup analyses of Bismuth type III-IV patients with R0 resection revealed that adjuvant chemotherapy produced significant survival benefits when compared with surgery alone (electronic supplementary Fig. S4); a similar result was reported by Im et al 53 However, a relatively low percentage of patients received adjuvant chemotherapy and there was a large difference in chemotherapy percentages between the LS and OP groups. A previous study demonstrated that LS is associated with greater rates of compliance with guidelines for adjuvant chemotherapy, as well as a slightly shorter time before initiation of chemotherapy.…”
Section: Discussionsupporting
confidence: 81%
“…Owing to the rarity of the disease, there remains a lack of randomized phase III data to guide decisions as far as the optimal adjuvant treatment, in particular with respect to RT 60. A number of single-institution retrospective studies and a multicenter retrospective study have suggested an improvement in OS for patients with resected cholangiocarcinoma who undergo any adjuvant therapy versus observation alone, in particular for patients with positive surgical margins or positive lymph nodes 61–66…”
Section: Methodsmentioning
confidence: 99%
“…In the postoperative setting, any gross residual disease, plus the tumor bed and high-risk elective lymph node regions, should be targeted 61,76,83,85,89,90,92,117. When delivered preoperatively, the primary tumor plus a margin should be targeted to include elective lymph node regions and microscopic disease extension, which can extend 1.0 to 2.0 cm beyond gross tumor 118,119.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations